Impact of Quantum Computing on Accounting Information Systems: Challenges and Opportunities - Kasheem, Majdy; Shalghoum, Najimudin; Abdullah, Mahmoud (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2025)
Quantum computing (QC) is an emerging technology that has the potential to revolutionize various industries, including accounting. This paper explores the impact of quantum computing on Accounting Information Systems (AIS), focusing on the challenges and opportunities it presents. With the exponential growth of data and increasing complexity in financial transactions, traditional AIS face limitations in processing power, speed, and data security. Quantum computing, with its ability to process vast amounts of data simultaneously and perform complex calculations, offers a solution to these challenges. By leveraging quantum algorithms, AIS could enhance data processing efficiency, improve financial modeling, and strengthen data security, particularly through quantum-safe encryption. However, the integration of QC into AIS also raises significant challenges, including the technical limitations of current quantum hardware, the potential disruption of existing cryptographic methods, and the lack of expertise in quantum technologies within the accounting profession. This paper examines these issues and discusses how accounting professionals and organizations can prepare for the future integration of QC into AIS. As quantum computing continues to evolve, its application to AIS holds promise for transforming the accounting industry by improving the accuracy, speed, and security of financial systems.